2019
DOI: 10.7759/cureus.6169
|View full text |Cite
|
Sign up to set email alerts
|

Student's Knowledge, Attitudes, and Practices Related to Cardiopulmonary Resuscitation at Qassim University, Saudi Arabia

Abstract: BackgroundCardiopulmonary resuscitation (CPR) is a lifesaving technique that is vital to deal with in many emergencies. Early interference with the cardiopulmonary resuscitation technique is really important for the survival of the patient. This study assesses the level of knowledge, attitudes, and practices regarding CPR among Qassim University students.Materials and methodsA cross-sectional study was conducted at Qassim University. The sample was university students. The colleges were chosen by a simple rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
4
10
0
Order By: Relevance
“…The results showed that the gender had not an apparent effect on knowledge level. Similar result reported form Saudi Arabia [14] but another studies in France showed a difference between males and females [17]. In contrast to gender, the results showed that attendance a BLS course previously had signi cant effect on knowledge level.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results showed that the gender had not an apparent effect on knowledge level. Similar result reported form Saudi Arabia [14] but another studies in France showed a difference between males and females [17]. In contrast to gender, the results showed that attendance a BLS course previously had signi cant effect on knowledge level.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, Jordan has a better education system. Regarding BLS training, the results showed that 21.7% of the participants stated that they had received BLS training, lower than that reported in Oman (35.2%), [13] Egypt (27%) [6] and Saudi Arabia (22.5%) [14] comparable to data reported elsewhere, including India (18.9%) [10] and Pakistan (14.7%) [15]. All health-care staff in the US were recommended to receive BLS training routinely since 1966.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Numerous reports have examined the knowledge and attitudes of BLS among health profession students in different countries, including Pakistan [ 7 ], India [ 8 ], Nigeria [ 9 ], Egypt [ 10 ], and the UK [ 11 ]. Similarly, studies in Saudi Arabia assessed BLS knowledge among medical students in Qassim University [ 12 ], Jouf University [ 13 ], Princess Noura University [ 14 ], Jizan University [ 15 ], and King Khalid University [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of a longitudinal CPR elective improved resuscitation science education for medical students and fostered increased community CPR training [ 7 ]. incorporation of a BLS course, including CPR learning procedures in the university curriculum, with regular reassessments, would increase the knowledge and application of CPR skills among students for saving people's life [ 8 - 9 ].…”
Section: Introductionmentioning
confidence: 99%